Sounds, songs and music of south India - Karnesvaran S; Manoharan S (Journal of All India Institute of Speech and Hearing, 1970)
Music has been a cultivated art in India for the last 3000 years.   The chant is essential element of the Vedic ritual.   Reference in the later Vedic literature, the Buddhist pictures and the Brahmanical epics show that it was highly developed as a secular art in the centuries preceding the beginning of the Christian Era (Coomaraswamy, 1968).